The frequency of occult cervical metastasis in oral squamous cell carcinoma patients - A cross sectional study - Ahmad Abdul Haseeb; Ashfaq Ur Rahim; Saud Iqbal; Humaira Batool; Samreen Younas; Hafiz Muhammad Jawaad Manzoor (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the frequency of occult cervical metastasis in oral squamous cell carcinoma patients. Methods: This cross sectional study was conducted in the department of maxillofacial surgery, Mayo Hospital, Lahore from July 31st, 2015 to January 31st, 2016 on 100 patients of oral Squamous Cell Carcinoma (SCC) having clinically and radiologically negative nodes. Prophylactic functional neck dissection was done in each patient and was sent to the pathology lab for evaluation of any occult metastasis. Results: Overall frequency of occult cervical metastasis was found to be 27%. In 41(41 %) specimens of SCC of tongue, 13(31.7%) had occult metastasis. In Alveolar mucosa occult metastasis was found in 4(20 %) out of 20(20 %) patients. In SCC of buccal mucosa occult metastasis was found in 10(29.4%) out of 34(34 %) patients. In SCC of lip no occult metastasis was detected. Conclusion: Within the boundaries of the present study, it is concluded that occult cervical metastasis was most frequent in cases of SCC tongue, whereas no occult cervical metastasis detected in SCC of lip. Key Words: Squamous cell carcinoma, cervical lymph nodes, prophylactic neck dissection, occult cervical metastasis. Continuous...